THE EFFECT OF USING STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) ON STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT AT THE TENTH GRADE OF MAS MIFTAHUL ‘ULUMI SYAR’IYYAH CANDUANG - Jannah, Miftahul; Melani, Melyann; Reflinda; Roza, Veni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was due to discover the effect of using Student Team Achievement Divisions (STAD) towards students’ reading comprehension on narrative text. There were some problems that researcher found during the preliminary research. The students have a low reading comprehension ability, low reading interest, the students felt that reading is a boring activity and the teacher applied a monotonous method. This research was a quasi-experimental design by using pre-test and post-test control grup design. The population was the tenth grade students consisted of 41 students. The sample was X.1 consisted of 20 students as the experiment class and X.2 consisted of 21 students as the control class. The reading test was used as the research instrument. The researcher utilized SPSS version 26 to analyze the data. The result showed the significant effect of using STAD method towards students’ reading comprehension on narrative text. It has presented by using statistical of paired sample t-test where Sig. (2-tailed) was 0,000 < 0,05 it means that Ha is accepted. In addition, there was significant difference of using STAD and without using STAD. It can be seen from the statistical of independent sample t-test, where Sig. (2-tailed) was 0,025 < 0,05 it means that H0 not accept. Furthermore, it can be concluded that the use of STAD method is more effective than using lecture method to improve students’ reading comprehension.